Sufiks Infleksional dalam Bahasa Uab Meto Rumpun L: Kajian Morfologis - Efron Erwin Yohanis Loe; Dian Rahmani Putri (Sasdaya: Gadjah Mada Journal of Humanities, 2025)
The title of this article is Inflectional Suffix in Uab Meto Language Cluster L: Morphological Approach. The aim of this research is to find out and to describe the types of inflectional morphology and the grammatical meaning in Uab Meto language cluster L. Uab Meto Language consist of two types namely Uab Meto cluster L andUab Meto cluster R with their area speakers. The focus of this research is Uab Meto language clusters L, used in Bijaepunu Village, North Molo District, South Central Timor Regency, East Nusa Tenggara Province. Theoretical approach is used in thisresearch is morphology by Aronoff and Fudeman 2011 to solve the research problems. The research method used is descriptive qualitative. The research data is obtained used the observation and interlocution method. The data collected are interviewing and recording from informants as the native speaker of Uab Meto language cluster L. The researcher find out three types of inflectional morphology in Uab Meto language cluster L, theyare suffix /-n/, /-in/ and /-sin/. These suffixusing in noun and verb. The using of suffix /-n/, /-in/, and /-sin/ that follows with deletion and displacement of phoneme. The result analysis of the third suffixes /-n/, /-in/ and /-sin/ shows that, the grammatical meaning of these suffix is plural meaning when added to lexeme base and it is to describe the object more then one and the action is doing more then a times.